Pro Web Project Management - Emond, Justin; Steins, Chris; SpringerLink (Online service) (Berkeley, CA : Apress, 2011)
Pro Web Project Management is a collection of hard-won lessons the authors have learned managing modern web projects with small and medium budgets in a consulting environment. This isn$1 (Bt a book about project management theory. Pro Web Project Management tells how to create real deliverables, get answers from indecisive clients, manage wayward programmers, and use checklists to wow clients. This book is made up of real examples, real lessons, real documents, and real tips woven together into a step-by-step walkthrough of a project's life cycle. Pro Web Project Management is written for both the full-time project manager and the aspiring project manager who might have a role that blends client support, web development, and project management. The project budget sweet spot for this book is $50,000 to $500,000. If you manage a project in this space, reading this book will make you a better project manager. Learn how to manage a modern web project with a budget of $50,000 to $500,000 Get actionable tips on dealing with real project management challenges Learn the simple, defined process$1 (Brefined over the years$1 (Bto take simple and complex projects from proposal to successful launchs
Keywords: Computer science; Computer Science; Computer Science, general